(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In this article, on the basis of a small survey, the difficulties faced by Russian-speaking students studying the Turkish language are revealed. According to the results of the survey, topical problems and tasks for the study of the Turkish language were identified and solved. The article deals with the issues of facilitating and accelerating the study of the Turkish language by Russian-speaking students.